Platelet-Derived Microparticle Count in Î²-Thalassemia Patients with Direct Labeling Monoclonal Antibody CD62P and CD41 (Majalah Kedokteran Bandung, 2020)
Thromboembolic events are potentially life-threatening clinical complications found in Î²-thalassemia patients. The pathogenesis of the hypercoagulable state in Î²-thalassemia patients results from the degradation of excess Î±-globin chains in red blood cells, leading to intracellular labile iron accumulation, oxidative stress, and more rigid, deformed, and eventually prematurely damaged red blood cells. This process is associated with the loss of the normal asymmetrical distribution of membrane phosphatidylserine and its exposure to the outer surface of the blood cell membrane resulting in the formation of tenase complexes, prothrombinase, and thrombin complexes. Increased thrombins lead to platelet activation and platelet-derived microparticles synthesis, which in turn contributes to thrombus formation. This study aimed to determine the increase in the platelet-derived microparticle count by direct labeling of CD62P and CD41 monoclonal antibodies in Î²-thalassemia patients when compared with normal subjects. This was a cross-sectional analytical quantitative study conducted in Dr. Hasan Sadikin General Hospital Bandung and Dharmais Cancer Hospital Jakarta Indonesia between August and September 2019. Sixty patients, divided evenly into Î²-thalassemia group and control group, were labeled by CD62P and CD41 monoclonal antibodies. Results showed that the Î²-thalassemia group had a platelet count of 197x103/uL (58–1,261) with a median count for platelet-derived microparticles of 10,553 events/uL (779–90,971) as opposed to 1,861 events/uL (1,244–3,174) in the normal group (p
Keywords: hypercoagulation; monoclonal antibodies; phosphatidylserine; platelet derived microparticles; thalassemia.